PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN (Studi pada Konsumen Waroeng Steak and Shake cabang Ngesrep) - Pratama Wardana, Dimas Aditya; DS, Agus Hermani (Jurnal Ilmu Administrasi Bisnis, 2020)
Nowadays, the development of business in the culinary sector, especially restaurants berkembangan more rapidly, because food is a basic requirement. Waroeng Steak and Shake is one of the businesses in this area and has opened many branches one in Ngesrep because Ngesrep is a strategic place because it was near the office and the university. Along the way, Waroeng Steak and Shake received numerous complaints from consumers who are not satisfied and result in a decrease in the number of sales. This research has the goal to determine the effect of quality of service and product quality to customer satisfaction. This type of research is explanatory research, samples taken by 100 respondents who had made purchases transaction at Waroeng Steak and Shake, 17 years old for minimum, and domicilized at Semarang either temporarily or permanently. The sampling technique used is purposive sampling and data collection techniques used are questionnaires. The study consists of 3 variables, 20 indicators, and 3 hypotheses. The instrument analysis is used SPSS 21 for Windows to test the validity, reliability test, correlation coefficient, coefficient of determination, simple and multiple regression analysis and significance test (t test and F). These results indicate that partial service quality and significant positive effect on customer satisfaction with the results of Y = 3.363 + 0,514X1 and product quality and significant positive effect on customer satisfaction with the results of Y = 5.689 + 1,166X2. As well as the quality of service and product quality simultaneously positive and significant impact on consumer satisfaction with the results of Y = 0.982 + 0,276X1 + 0,763X2. With a coefficient of determination of 59.1% X1 and X2 by 65%. Based on these results can disumpulkan that the quality of service and product quality Waroeng Steak and Shake is good, but should be improved, there are still mindless consumer complaints related to quality of service and product quality. utamannya service quality improvements with regard to speed of service, responsiveness of employees, clarity of information delivery, comfort rooms and supporting facilities are more available. Waroeng Steak and Shake also need to improve the quality of products, especially in terms of the portions served and ways of presenting food and miuman to consumers.